Integrating research into a molecular cloning course to address the evolving biotechnology landscape. Issue 1 (27th July 2020) - Garcia, Christina B.; Chapman, Ian F.; Chen, Stefanie H.; Lazear, Eric; Lentz, Thomas B.; Williams, Christina; Dums, Jacob T.; Goller, Carlos C.; Robertson, Sabrina D.
Abstract: The rapid development of molecular biotechnology presents a curricular challenge for educators trying to provide students with relevant coursework. A comprehensive biology education should also include opportunities for students to develop intellectual and technical skills through authentic research experiences. Integrating relevant and interesting research projects into their classes, however, can be a challenging task for instructors. To address these varied demands, we redesigned our existing molecular cloning course to incorporate an independent research project assessing calcium signaling. In the revised course, students use traditional and recombination‐based cloning strategies to generate bacterial and mammalian expression vectors encoding CaMPARI, a novel fluorescent calcium indicator. Bacterially‐expressed CaMPARI is used in protein quantification and purification assays. Students must also design their own research project evaluating the effect of chemotherapeutic agents on calcium signaling in a mammalian system. Revised and novel labs were designed to be modular, facilitating their integration into the course over 2 years. End‐of‐semester student evaluations were compared between years revealing a significant difference in students' perception of the course's difficulty between years. This change in attitude highlights potential pedagogical considerations that must be examined when introducing new material and activities into existing courses. Since calcium signaling is important for cellular process across diverse species, instructors may be able to develop research projects within their respective areas of interest. Integration of authentic research experiences into the curriculum is challenging; however, the framework described here provides a versatile structure that can be adapted to merge diverse instructor interests with evolving educational needs.